“ARAJANNA SOPPENG” MENURUT CERITA RAKYAT - Hary Sumange (WalennaE, 2001)
Apparently arajang has been inadequately interpreted. Arajang which refers to ornaments or regalia are misleading, since Bugis ancestors had interpreted it as small kingdom. It was Arajang which possessed power, as Tomanurung representation after its vanished (mallajang). Arung Bila, Tomanurung replacement, was arajang task officers. King and his people contract within constitutional monarchy governmental system of Soppeng Kingdom were known with the term mallamungmpatu. The system was based on the principal belief: mangle passing, massongmpawo or to unite lower inspirations with upper policies.